Satellite Communication and Navigation Integrated Signal - Junxia Cui; Huli Shi (Institute of Advanced Engineering and Science, 2013)
Under the rapid development of satellite communication systems and satellite navigation systems, there is an urgent need to combine the two together in order to achieve location-based services, etc. Despite the long relationship history of navigation and communication, the two satellite systems are basically independent of each other. As a result, terminal size tends to be relatively large, and difficult to be miniaturized. This article puts forward a novel idea that satellite navigation and satellite communication functions are integrated together in the signal level, and gives four types of the integrated navigation and communication signal structures which are composed of message, spreading code and carrier. It lays a technical foundation for the in-depth development of the integration of navigation and communication systems in signal level. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3034